A Placebo-Controlled Trial of Constraint-Induced Movement Therapy for Upper Extremity After Stroke - Taub, Edward; Uswatte, Gitendra; King, Danna Kay; Morris, David; Crago, Jean E.; Chatterjee, Anjan (Stroke (1970), 2006)
Background and Purpose— Constraint-Induced Movement therapy (CI therapy) is a neurorehabilitation technique developed to improve use of the more affected upper extremity after stroke. A number of studies have reported positive effects for this intervention, but an experiment with a credible placebo control group has not yet been published. Methods— We conducted a placebo-controlled trial of CI therapy in patients with mild to moderate chronic (mean=4.5 years after stroke) motor deficit after stroke. The CI therapy group received intensive training (shaping) of the more affected upper extremity for 6 hours per day on 10 consecutive weekdays, restraint of the less affected extremity for a target of 90% of waking hours during the 2-week treatment period, and application of a number of other techniques designed to produce transfer to the life situation. The placebo group received a program of physical fitness, cognitive, and relaxation exercises for the same length of time and with the same amount of therapist interaction as the experimental group. Results— After CI therapy, patients showed large (Wolf Motor Function Test) to very large improvements in the functional use of their more affected arm in their daily lives (Motor Activity Log; P <0.0001). The changes persisted over the 2 years tested. Placebo subjects showed no significant changes. Conclusion— The results support the efficacy of CI therapy for rehabilitating upper extremity motor function in patients with chronic stroke.